Manganese Removal In Groundwater Treatment Using High Grade Limestone - Abdul Rahim, Ainul Afeeqah Athirah (Universiti Sains Malaysia, 2018)
Manganese is one of difficult elements to remove in groundwater due to its high solubility in both acid and neutral condition. However, limestone is effective in removing Manganese if the Manganese is in low concentration. This study investigate the groundwater treatment using high purity limestone in removing Manganese. In this research, the characterization of limestone sample obtained from Ipoh was done. The limestone sample contain CaCO3 in majority at 97.3%. Groundwater sample obtained from USM’s Engineering Campus also characterized and the concentration of Manganese is approximately 0.5 ppm exceeding the Raw Water Quality Standard at 0.1 ppm. Filtration of groundwater using pebble size limestone and sand size limestone column filter was done with different flowrate. For pebble size limestone column filter, the highest percentage removal is 58.15% where the flowrate is 0.007 L/s. On the other hand, for sand size limestone column filter, the highest percentage removal is 97.26% where the flowrate is 0.017 L/s. Fine size limestone particle shows an efficient Manganese removal in groundwater compared to coarser size particle. This was most probably due to the high surface area of smaller particle. The flow rate did not shows any significant trend in removing Manganese.